Geology and Wine 13. Geographic Information System Characterization of Four Appellations in West Texas, USA - Hellman, Edward; Takow, Elvis; Tchakerian, Maria; Coulson, Robert (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2011)
SUMMARY Texas produces approximately 90 000 hl of wine annually from more than 200 wineries and 1214 ha of vineyards. Eight wine grape production regions are officially recognized as American Viticultural Areas (AVAs) in Texas. Improved understanding of the growing conditions within each AVA facilitates selection of well-adapted cultivars that is critical for continued success and expansion of the wine industry. A geographic information system (GIS) was developed to enable enhanced characterization of the climatic, geologic and edaphic conditions of Texas AVAs. The GIS contains datasets describing climatic variables, geology, soils, elevation and topography, all of significance to grape production. This paper characterizes the four viticultural areas (AVAs) of west Texas: Texas High Plains AVA, Escondido Valley AVA, Texas Davis Mountains AVA, and Mesilla Valley AVA. Common features of the four AVAs are relatively high elevation, warm to very warm growing-season temperatures, mild winter temperatures, and low annual precipitation. Local differences in elevation and topography modify climatic conditions among AVAs, providing variations in growing degree-days and ripening-period mean temperatures that influence the performance of grape cultivars. The Texas High Plains and Texas Davis Mountains AVAs have the lowest growing degree-days and coolest ripening-period mean temperatures; Escondido Valley and Mesilla Valley AVAs are drier and warmer, resulting in fruit ripening earlier than in the High Plains and Davis Mountains AVAs. Variable underlying geology leads to differing soil types planted to vineyards in each AVA; predominantly loamy fine sands and fine sandy loam in Texas High Plains, silty clay loam and loam in Escondido Valley, loam and clay loam in Texas Davis Mountains, and clay loam and sandy loam in Mesilla Valley. West Texas produces red wines from Cabernet Sauvignon and Merlot cultivars, which are notable for good tannin and excellent colour; recent planting trends to warm-climate cultivars, including Tempranillo, Sangiovese, Mourvèdre, and Grenache, are producing blended wines of great promise. Similarly, a solid reputation for white wines from Chenin blanc and Chardonnay is being enhanced by increased production of Viognier, Vermentino, and other warm-climate varietal wines.